Haemato-biochemical and antioxidant profiling of indigenous cattle of Kashmir (SAARC Journal of Agriculture, 2016)
Kashmir falls in the great north-western complex of the Himalayan ranges, at 34o North and 76o East with an average altitude of 1850 metres amsl. Indigenous cattle constitute 51% of total cattle population of the State. The evaluation of some important blood parameters in indigenous cattle for assessment of animal health status as well as course of variation in blood parameters in these animals was undertaken during summer to autumn, 2014. Twenty two indigenous cattle from different pockets of Kashmir valley were studied for haematobiochemical and anti-oxidative parameters. The values recorded for Hb, PCV and MCV (10.97 ±0.22 g dl-1, 36.45±0.55 %, and 67.71±1.76 fl) respectively were on the higher side when compared to crossbreds or exotic cattle. TBARS and FRAP, measures of oxidant-antioxidant balance were 5.90 ±0.39 n ML-1 and 548.16±23.78 ? ML-1 respectively, the values were on higher side when compared to exotic breeds. Similarly total protein, albumin and globulin levels reported were - 8.27±0.22 g dl-1, 3.31±0.07 g dl-1 and 4.95±0.20 gdl-1 respectively that stands higher when compared to the reference values for cattle.Plasma biochemical analytes urea, creatinine, triglycerides, AST and ALT recorded in present study were comparable to the reference values for cattle. All these parameters provide complementary information about the homeostasis of indigenous cattle and indicate its good health status, higher disease resistance and good metabolic defence as compared to exotic or crossbred cattle in its temperate climate.SAARC J. Agri., 13(2): 26-33 (2015)